Addressing Hunger and Starvation in Situations of Armed Conflict — Laying the Foundations for Peace. (17th January 2020) - Lander, Brian; Richards, Rebecca Vetharaniam
Abstract: Food is a common denominator for human survival and is often the source of national pride and cultural significance. Yet, famine and starvation remain a real threat to millions of people around the world. This article sets the scene for an exploration of the relationship between food and security within conflict settings and of how the response of humanitarian actors can pave the way for improving the prospects for peace. Through examining the trends that are impacting the food security of civilians, including humanitarian access and attacks against objects indispensable to the survival of these populations and against humanitarian workers, this article considers the linkages between hunger and conflict as well as the avenues that must be pursued to prevent and end conflicts. Focus is given to the contributions of organizations like the United Nations World Food Programme (WFP) to address underlying root causes in an inclusive, integrated and sustainable manner. The available tools such organizations have at their disposal are also considered, highlighting the need for a more comprehensive framework that builds on existing legal foundations, international commitments, and the efforts of humanitarian, development and peace actors. The engagement of the international community in averting famine, relapse into conflict and exacerbation of conflict through food insecurity requires a multi-faceted response given the nature of famine and starvation in the world today. The article concludes with thoughts on ways of utilizing existing rules and frameworks to protect civilians from starvation in times of armed conflict.